Sexualidad, moral y cuentas falsas. Usos políticos de la edad de la primera relación sexual en Chile. - Palma, Irma (Nomadías, 2013)
This article makes a methodological and political discussion on the measurement of the age of first intercourse in national surveys, analyzes the use of the statistical instruments, discusses certain theses and interpretations, and uses of the research performed by researchers in the field of gender studies and by catholic academic institutions. It shows that part of the background research presents statistical errors in the measurement, which leads to erroneous conclusions. Nevertheless, it is used. It claims that this is a technical, academic and political issue in a context where surveys have become in contemporary societies in basis of policy making, in instruments of public debate, or as reference in institutional reflexivity.